Analisis Kehilangan Air Pada Jaringan Utama Daerah Irigasi Toraut - Muhamad Rizadi Laili; Barry Yusuf Labdul; Rawiyah Husnan (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
The agricultural sector plays a crucial role in realizing Asta Cita's vision of food security, one of which is through the optimization of the Toraut Dam in Toraut Utara Village. However, increasing water demand for rice field intensification and expansion, alongside limited irrigation water supply, necessitates efficient irrigation system management. This research aims to analyze water loss in the distribution of irrigation networks in the Toraut Irrigation Area. The study used primary data (cross-sectional geometry and canal flow velocity measured using the surface buoy method) and secondary data (climatological records, irrigation network maps, and supporting documents). The analysis included calculating flow discharge, water loss due to evaporation using the Penman method, seepage, irrigation efficiency, and water loss in each channel segment. Results showed the highest discharge in the primary channel was at SPKr I upstream (5.586 m³/s), and the lowest was at SPKr 7 downstream (0.136 m³/s). In the secondary channel, the highest discharge was found at Secondary Tumpah upstream (0.895 m³/s), while the lowest was at Secondary Dumara downstream (0.043 m³/s). The highest efficiency in the primary channel was at SPKn (98.55%), while the lowest was at SPKr 6 (70.15%). In the secondary channels, the highest efficiency was at Secondary Tongot 2 (97.76%), and the lowest at Secondary Dumara (35.87%). The greatest water loss in the primary channel occurred at SPKr 6 (29.85%), and the least at SPKn (1.45%). For secondary channels, the greatest water loss occurred in Secondary Dumara (64.13%) and the least in Secondary Tondait (0.75%).